Representation of Seniority Role in Animated Video “ Anima Si Nopal” - Merlina Fatimah Nasruddin (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Seniority Role is a social phenomenon that has long been embedded in the social life of the Indonesian people. Indonesian people uphold politeness and respect for older people in interacting in their daily lives. The level in the aspect of age is the most visible feature applied in various environments. Regardless of the morally good or bad behavior of older people, younger people tend to be more guarded. On the other hand, older people tend to be more dominant. The world of animated films today has been enlivened by local animation whose popularity is not inferior to animation made by well-known studios. Local animation is a work that deserves appreciation because it can emerge from a small studio with a very personal style representing the creator. In addition to being an indicator of the achievement of national animation film technology, local animation is also able to represent the social phenomena and phenomena of society at the time the animation was broadcast. Characters that appear in animated films can represent characteristics in terms of physical and mental and emotional society in general at that time. This research produces a qualitative analysis to examine the social relationship in terms of ageism between the character Nopal and his sister Cutie. What is going on in the relationship between Nopal and Cutie when they function as brother and sister roles. Preliminary data involve three episodes of Animasinopal animated video. The method used is visual language.